Twenty Miscellaneous New Species and One New Nothogenus and Nothospecies in Brazilian Bromeliaceae - Leme, Elton M. C.; Souza, Everton Hilo De; Till, Walter; Barfuss, Michael H. J.; Filho, José Alves Siqueira; Kollmann, Ludovic J.c.; Couto, Dayvid R.; Fraga, Claudio Nicoletti De; Fontana, André P.; Farias-Castro, Antônio S.; Silva, João B. Fernandes Da (Phytotaxa, 2025)
The authors describe and illustrate 20 new species and one new nothogenus and nothospecies in Bromeliaceae, encompassing 12 genera and one nothogenus, in the subfamily Bromelioideae (Aechmea cunhambebensis, A. marcpignalii, Bromelia boqueiranensis, B. nordestina, B. saracataquerensis, Cryptanthus cajuitensis, C. spathulatifolius, Hohenbergia kollmannii, Orthophytum afonsoclaudense, O. pseudoestevesii, Portea santosiana, Wittrockia organensis, and X Nidunelia rodrigoana), Pitcairnioideae (Dyckia albolutea, D. flabellata, Encholirium inhaiensis, and Pitcairnia kranziana), and Tillandsioideae (Tillandsia montezumensis, T. tephrosa, Vriesea punctatissima, and V. ilhagrandensis). A discussion about the diagnostic morphological characteristics of these taxa and their affinities is provided, as well as notes on their geographic distribution and natural history.